A computational fluid dynamics study of turbulence, radiation, and combustion models for natural gas combustion burner - Pang, Y.S.; Law, Woon Phui; Pung, K.Q.; Jolius, Gimbun (Department of Chemical Engineering, Diponegoro University, 2018)
This paper presents a Computational Fluid Dynamics (CFD) study of a natural gas combustion burner focusing on the effect of combustion, thermal radiation and turbulence models on the temperature and chemical species con-centration fields. The combustion was modelled using the finite rate/eddy dissipation (FR/EDM) and partially pre-mixed flame models. Detailed chemistry kinetics CHEMKIN GRI-MECH 3.0 consisting of 325 reactions was em-ployed to model the methane combustion. Discrete ordinates (DO) and spherical harmonics (P1) model were em-ployed to predict the thermal radiation. The gas absorption coefficient dependence on the wavelength is resolved by the weighted-sum-of-gray-gases model (WSGGM). Turbulence flow was simulated using Reynolds-averaged Na-vier-Stokes (RANS) based models. The findings showed that a combination of partially premixed flame, P1 and standard k-ε (SKE) gave the most accurate prediction with an average deviation of around 7.8% of combustion temperature and 15.5% for reactant composition (methane and oxygen). The results show the multi-step chemistry in the partially premixed model is more accurate than the two-step FR/EDM. Meanwhile, inclusion of thermal ra-diation has a minor effect on the heat transfer and species concentration. SKE turbulence model yielded better prediction compared to the realizable k-ε (RKE) and renormalized k-ε (RNG). The CFD simulation presented in this work may serve as a useful tool to evaluate a performance of a natural gas combustor.